HIỆN TRẠNG XÓI LỞ - BỒI TỤ BỜ BIỂN TỈNH BÌNH THUẬN - Trung, Phạm Bá; Mầu, Lê Đình (Vietnam Journal of Earth Sciences, 2011)
Status of erosion - deposition processes along the coast of BinhThuan ProvinceThis paper presents the status of erosion - deposition processes along the coast of Binhthuan Province. Data on shoreline change was taken from field investigation and scientific reports of different projects, which were carried out by Institute of Oceanography. Study results show that the coastline along study area is mainly subjected to erosion during NE monsoon period, whereas, during SW monsoon period it is subjected to accretion, but the magnitude of erosion is larger than that of the accretion. At present, almost serious eroded shoreline sections and river mouth along the study coast have been protected by hardstructures; and the erosion - deposition processes occurred mainly due to the impact of protected structures. There are many impacts on the erosion - deposition processes due to the mistake in designation of the protected structure. To date, there are not any measures to maintain the normal operation of protected structures, as well as in reduction the impact of protected structures to adjacent environment.